Engineering of a linear inactive analog of human β‐defensin 4 to generate peptides with potent antimicrobial activity. (24th March 2015) - Sharma, Himanshu; Mathew, Basil; Nagaraj, Ramakrishnan
<x xml:space="preserve">Abstract</x> Human β‐defensins (HBDs) are cationic antimicrobial peptides constrained by three disulfide bridges. They have diverse range of functions in the innate immune response. It is of interest to investigate whether linear analogs of defensins can be generated, which possess antimicrobial activity. In this study, we have designed linear peptides with potent antimicrobial activity from an inactive peptide spanning the N‐terminus of HBD4. Our results show that l‐arginine to d‐arginine substitution imparts considerable antimicrobial activity against both bacteria and Candida albicans. Increase in hydrophobicity by fatty acylation of the peptides with myristic acid further enhances their potency. In the presence of high concentrations of salt, antimicrobial activity of the myristoylated peptide with l‐arginine is attenuated relatively to a lesser extent as compared with the linear active peptide with d‐arginine. Substitution of cysteine with the hydrophobic helix‐promoting amino acid α‐aminoisobutyric acid favors candidacidal activity but not antibacterial activity. The mechanism of killing by d‐arginine substituted unacylated analog involves transient interaction with the bacterial membrane followed by translocation into the cytoplasm without membrane permeabilization. Accumulation of peptides in the cytoplasm can affect various cellular processes that lead to cell death. However, the peptide causes membrane permeabilization in case of C. albicans. Myristoylation results in greater interaction of the peptide chain with the microbial cell surface and causes membrane permeabilization. Results described in the study demonstrate that it is possible to generate highly active linear analogs of defensins by selective introduction of d‐amino acids and fatty acids, which could be attractive candidates for development as therapeutic agents. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.